PD-1 inhibitors plus nab-paclitaxel-containing chemotherapy for advanced gallbladder cancer in a second-line setting: A retrospective analysis of a case series - Tan, Sirui; Yu, Jing; Huang, Qiyue; Zhou, Nan; Gou, Hongfeng (Frontiers in Oncology, 2022)
Background: Gallbladder cancer (GBC) is a fatal cancer, and the efficacy of the current standard second-line chemotherapy in this patient population is limited. Novel therapies need to be explored. The study was aimed to investigate the efﬁcacy and safety of PD-1 inhibitors combined with nab-paclitaxel-based chemotherapy for advanced GBC in second-line setting. Methods: Between April 2020 and May 2022, the patients with advanced GBC receiving programmed cell death 1 (PD-1) inhibitors combined with nab-paclitaxel-based chemotherapy after resistance to first-line gemcitabine-based chemotherapy at West China Hospital were retrospectively screened. Results: Eleven patients were included and all received gemcitabine-based chemotherapy as first-line therapy. Eight patients underwent NGS testing, and all had microsatellite stability (MSS) and a low tumor mutation burden (TMB). Six patients were negative for programmed cell death 1-ligand 1 (PD-L1) expression and one patient was positive for PD-L1. Therapeutically relevant genetic alterations were not found. All patients received PD-1 inhibitors in combination with nab-paclitaxel-based chemotherapy as second-line therapy. Pembrolizumab was administered in 3 patients, and sintilimab was administered in eight patients. One patient had no measurable target lesion. One (10.0%) patient achieved complete response (CR), four (40%) patients achieved partial response (PR), and four (40%) patients achieved stable disease (SD). The median progression-free survival (PFS) was 7.5 (95% CI: 2.5-12.5) months and the median overall survival (OS) was 12.7 (95% CI: 5.5-19.9) months. The adverse events (AEs) were manageable. Conclusion: Our results suggest that PD-1 inhibitors combined with nab-paclitaxel-based chemotherapy as second-line therapy for advanced GBC might be a potential treatment and deserve further evaluation.